Studi Eksperimen Peningkatan Mutu Gambar Dengan Menggunakan Metode Bercerita Pada Murid-murid TK Indrayasana Maguwoharjo Yogyakarta - Arundati Shinta, Esti Listiari, & Bimono (Jurnal Psikologi, 2005)
Children's drawing is not only an immediate visual image, but it can be an expression of a concept from an object or situation. Therefore children are able to produce drawings without seeing the real object. This experiment is conducted through 7 times story telling as the drawing's stimulus. There are 37 kindergarten children participate on this experiment. There are 5 aspects of drawing evaluation i.e. object color arrangement, figure movement, drawing theme, background color arrangement, and complexity. The comparison between the pre-test and post-test indicate that color arrangement either on object or background develops better among more than 50% students, whereas the other 3 drawing aspects are less likely to develop. It means that those story telling are insufficient on developing children's drawing imagination. It is because they need more on drawing with having example than listening story telling. On the other hand, the color development is more likely influenced by researcher's guidance on how to draw properly than story telling interventions.